Law Enforcement of Unregistered Marriage Practices in Indonesia Lawrence Meir Friedman's Legal Effective Perspective - Harry Pribadi Garfes (Badan Strategi Kebijakan Hukum, 2022)
Unregistered marriage is an endless problem with non-optimal law enforcement. Meanwhile, the massive impact of unregistered marriage is dangerous and this practice is not committed by one or two people but involves many parties. This research aims to describe parties involved in unregistered marriages and their respective roles. In addition, it provides information regarding unregistered marriage regulations and sanctions and determines law enforcement for the parties involved. This normative research used case approach and statutory approach. The data collection technique is documentation and the analysis technique is deductive and inductive. The results of this study found several parties involved in unregistered marriages. These parties are: first, main actors such as illegal rulers, husbands, and wives or marriage guardians. Second, parties who participate, such as marriage witnesses, brokers, and jockeys. Unregistered marriages are regulated in chapter 1 paragraph (2), chapter 3 paragraphs (1 and 2) of Law no. 32/1954 concerning the enactment of Law no. 22 of 1946 concerning registration of marriages, divorces, and reconciliation in all regions outside Java and Madura, the sanctions are contained in chapter 4 and chapter 45 paragraph (1) letter (a) PP No. 9/1975 concerning the Implementation of Law no. 1/1974 on marriage. Law enforcement against the perpetrators of unregistered marriages has not been optimal.